Habitat models of wood-inhabiting fungi along a decay gradient of Norway spruce logs. (December 2015) - Rajala, Tiina; Tuomivirta, Tero; Pennanen, Taina; Mäkipää, Raisa
Abstract: Information on the habitat requirements of wood-inhabiting fungi is needed to understand the factors that affect their diversity. We applied culture-free DNA extraction and 454-pyrosequencing to study the mycobiota of decaying Norway spruce ( Picea abies ) logs in five unmanaged boreal forests. Fungal habitat preferences in respect of wood density gradient were then estimated with generalized additive mixed models. Fungal diversity and wood density were inversely related, i.e., OTU richness generally increased as the log became increasingly decomposed. White-rot fungi (e.g., Phellinus nigrolimitatus ) and members of Hyphodontia did not show a clear response to the wood-density gradient, whereas abundance of Phellinus viticola and brown-rot fungi (e.g., Fomitopsis pinicola, Antrodia serialis, Coniophora olivaceae ) peaked during intermediate decay and mycorrhizal fungi (e.g., Piloderma, Tylospora, Russula ) increased in the later stages. This information on fungal habitat requirements facilitates the development of management practices that preserve fungal diversity in managed forests. Highlights: Fungi inhabiting dead spruce were identified by 454-sequencing. Fungal richness increased with the loss of wood density. Brown-rot fungi peaked during intermediate and mycorrhizal fungi in the later decay stages. Modeled fungal habitat requirements can be applied in forest management planning.